2016
DOI: 10.5173/ceju.2016.893
|View full text |Cite
|
Sign up to set email alerts
|

Contrast enhanced ultrasound in urothelial carcinoma of urinary bladder: An underutilized staging and grading modality

Abstract: IntroductionTo evaluate contrast enhanced ultrasound (CEUS) as a modality to predict T stage of cancer of urinary bladder (CAUB) and to predict the grade of the tumor preoperatively.Material and methods110 patients with CAUB presenting to the Department of Urology at our institution between July 2014 and December 2015 underwent CEUS prior to endoscopic resection and the CEUS findings were compared with histopathology results.ResultsCEUS had a sensitivity of 75, 65 and 90% and specificity of 95, 85 and 92% in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Type A curve is defined by rapid and high peak enhancement and fast wash-out time, correlating well with high grade UCC. Type B is defined by an early enhancement peak but slow plateau and very slow wash-out time, correlating well with low grade UCC [ 15 ]. In our study, CEUS with TIC of SCCB showed wash-in time of 10 s, TTP of 33 s, SI of 62.7% and wash-out time > 60 s. This is similar to the results of high grade UCC with high SI and slow wash-out time as reported by Drudi et al in 2014 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Type A curve is defined by rapid and high peak enhancement and fast wash-out time, correlating well with high grade UCC. Type B is defined by an early enhancement peak but slow plateau and very slow wash-out time, correlating well with low grade UCC [ 15 ]. In our study, CEUS with TIC of SCCB showed wash-in time of 10 s, TTP of 33 s, SI of 62.7% and wash-out time > 60 s. This is similar to the results of high grade UCC with high SI and slow wash-out time as reported by Drudi et al in 2014 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two-Dimensional Ultrasonography (2D US) is a widely used and recommended method for evaluating hematuria and for staging, particularly in patients who have allergies to intravenous contrast agents and renal failure (Figure 1) [5, 1721]. However, according to some publications 2D US is not recommended for the staging of BCa because it may not reveal the true local depth of its invasion [1821]. Three-dimensional US provides BCa imaging in multiple planes, and may improve the accuracy of staging BCa [19].…”
Section: Introductionmentioning
confidence: 99%
“…CEUS is a new technique that uses microbubbles as a ultrasonographic contrast agent to determine the grade and stage of BCa [18]. The use of CEUS was investigated to predict T stage and grade of BCa prior to endoscopic resection in 110 patients suspected of BCa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiología. 2017.Se ha reportado una sensibilidad del 89-100% y especificidad del 80-87%,(28)(29)(30) para el diagnóstico de CV con cistoscopia virtual, en comparación con 87-100% y 75-95% de la cistoscopia óptica, respectivamente (12). La sensibilidad disminuye en lesiones menores de 3 cm al igual que en la sospecha de tumor in situ, en estos casos es más fiable la visualización directa de las lesiones (29).…”
unclassified